The contribution of technology and the forefront role of technical measures in the prevention of infection risk in the healthcare sector - Oddo, Antonio (La Medicina del Lavoro, 2016)
Protecting healthcare staff against the risk of infection caused by injuries when using sharp or pointed instruments has been placed – as a special, common and difficult type of “biological risk” – at the centre of attention in the investigations, studies and research conducted by various countries and subjects that have led to a convergence between the results able to influence European and supranational legislation.  This convergence of results is headed towards the recognition of the great potential of the role of technology and, more specifically, of the “protection devices” of paramount and essential importance, as “technical measures”, over the other, nevertheless important “organisational” and “personal” measures. The national and international results of the studies and research, as well as their corresponding conclusions, deserve special space in this journal, given the supranational legislative recognition they received in Directive 2010/32/EU. Indeed, this latter Directive, set forth and classified, with a system of absolutely mandatory regulations, the “Framework agreement” concluded between the organisations that are most representative of the hospital and healthcare sector for the “prevention of cut and prick injuries”. On the basis of the “European Union” treaty, Directive 2010/32/EU must be assimilated in the legal system of all the member States of this “Union” with appropriately sanctioned legal provisions in the event of breach by “employers” and/or “directors”. In this sense, with Legislative Decree no. 19 of 2014, Italy introduced a dedicated “criminal offence of danger” for the breach of “prevention” regulations intended to prevent the specific “biological risk” in question, regulations that have been incorporated into Legislative Decree 81/08 – “The Occupational Safety and Health Consolidation Act” with a special “Section” (X bis) dedicated exclusively to them.